1998
DOI: 10.1007/s002619900363
|View full text |Cite
|
Sign up to set email alerts
|

Water enema computed tomography (WE-CT) in the local staging of low colorectal neoplasms: comparison with transrectal ultrasound

Abstract: Background: To determine the accuracy of computed tomography performed with a water enema application (WE-CT) in the local staging of low colorectal neoplasms and to compare the results with those of transrectal ultrasonography (TRUS). Methods: Forty patients with low colorectal tumors were evaluated prospectively by CT with the simultaneous administration of a lukewarm rectal enema (0.5-1.5 L). Thin slices (5 mm) and intravenous application of iodinated contrast media were routinely used. TRUS was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We are aware of that, nevertheless feces always contains small bubbles of gas [7], it still can easily be misinterpreted as tumor [5], but we examined patients with diagnosed rectum cancer and the purpose of the examination was not the detection, but the staging of the tumor. Similarly to Caseiro-Alves et al [1] and Gazelle et al [3], we found that certain patients did not tolerate well the administration of water volume exceeding a certain level. To avoid patient discomfort and decrease risk of complication we decided to perform WE-CT examinations with a reduced dose (400 ± 500 ml) of water in those cases when the primary pathologic process was localized to the rectum.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We are aware of that, nevertheless feces always contains small bubbles of gas [7], it still can easily be misinterpreted as tumor [5], but we examined patients with diagnosed rectum cancer and the purpose of the examination was not the detection, but the staging of the tumor. Similarly to Caseiro-Alves et al [1] and Gazelle et al [3], we found that certain patients did not tolerate well the administration of water volume exceeding a certain level. To avoid patient discomfort and decrease risk of complication we decided to perform WE-CT examinations with a reduced dose (400 ± 500 ml) of water in those cases when the primary pathologic process was localized to the rectum.…”
Section: Discussionsupporting
confidence: 83%
“…Most authors proposed to perform a bowel-cleansing regimen prior to the WE-CT examination [2, 3, 5 ± 9], while some others did not apply it regularly [1,12]. The amount of water, introduced into the rectum during the examination was between 1000 and 2000 ml [1 ± 3, 5 ± 9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations